Development and validation of a novel assay to identify radiosensitizers that target nucleophosmin 1. Issue 13 (1st July 2015) - Penthala, Narsimha R.; Crooks, Peter A.; Freeman, Michael L.; Sekhar, Konjeti R.
Graphical abstract: Novel Western blot assay was developed and tested for its applicability in identifying radiosensitizers that target nucleophosmin 1 (NPM1). Extractability of pNPM1 was used as a measurement for identification of active compounds from a library of analogs synthesized based on the lead molecule, YTR107. Abstract: A series of indole analogs that are synthesized using the scaffold of a potent radiosensitizer, YTR107, were tested for their ability to alter the solubility of phosphorylated nucleophosmin 1 (pNPM1). NPM1 is critical for DNA double strand break (DSB) repair. In response to formation of DNA DSBs, phosphorylated T199 NPM1 binds to ubiquitinated chromatin, in a RNF8/RNF168-dependent manner, forming irradiation-induced foci (IRIF) that promote repair of DNA DSBs. A Western blot assay was developed using lead molecule, YTR107, for the purpose of screening newly synthesized molecules that target pNPM1 in irradiated cells. A colony formation assay was used to demonstrate the radiosensitization properties of the compounds. Compounds that enhanced the extractability of pNPM1 upon radiation treatment possessed radiosensitization properties.